2022
DOI: 10.1097/md.0000000000030075
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed hospital presentation for patients with acute stroke in Makkah: A cross-sectional study

Abstract: Despite the recent advancements in the treatment of acute ischemic stroke, the delayed patient arrival to emergency department or hospital serve as crucial factor for the selection of appropriate intervention program. This study was aimed to identify factors associated with late hospital arrival for patients with acute ischemic stroke in Makkah, Saudi Arabia. A prospective cross-sectional study was carried out at Al-Noor Specialist Hospital among 98 enrolled patients with the mean age of 60.4 ± 10.3 years over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Although in our study we found no differences in mortality when stratifying our sample by schooling, there is also evidence in the literature that lower schooling is associated with a higher risk of dying from stroke [18]. Also, formal work has been associated with earlier consultation at the time of acute stroke in the international literature, which is similar to what was found in our study [19]. Importantly, education may be related to work, as less educated people are also often those with higher unemployment rates and this may in turn influence this outcome [19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although in our study we found no differences in mortality when stratifying our sample by schooling, there is also evidence in the literature that lower schooling is associated with a higher risk of dying from stroke [18]. Also, formal work has been associated with earlier consultation at the time of acute stroke in the international literature, which is similar to what was found in our study [19]. Importantly, education may be related to work, as less educated people are also often those with higher unemployment rates and this may in turn influence this outcome [19].…”
Section: Discussionsupporting
confidence: 86%
“…Also, formal work has been associated with earlier consultation at the time of acute stroke in the international literature, which is similar to what was found in our study [19]. Importantly, education may be related to work, as less educated people are also often those with higher unemployment rates and this may in turn influence this outcome [19].…”
Section: Color Version Available Onlinesupporting
confidence: 89%
“…In Makkah, Saudi Arabia, a recent cross-sectional study was conducted in 2022 to evaluate the late hospital arrival of patients with acute ischemic stroke. It was discovered that 45% of patients presented late and 55% of patients presented early [ 13 ].…”
Section: Introductionmentioning
confidence: 99%